Evaluation of varieties and hybrids of elephant grass Pennisetum purpureum and Pennisetum purpureum x Pennisetum glaucum for forages production - Martínez, R. O.; González, C. (Cuban Journal of Agricultural Science, 2018)
With the objective of knowing the productive performance under the climatic conditions of Mayabeque province in western Cuba, six varieties of elephant grass, three of Pennisetum purpureum (Morado, King grass, and Cuba CT-169) and three hybrids of Pennisetum purpureum x Pennisetum glaucum (Cuba OM-22, H-1 and H-2) were evaluated. A randomized block design was used in five plots of 5x5 m2, in red Ferralitic soil. The cuts of the dry season were made every 90 days, those of the rainy season were made every 60 days. Fertilization at a rate of 250 Kg of N/ha/year in urea form was applied. During the dry season it was irrigated every 15 days with a standard of 250m3/ha. The production of DM /h /year was 23.1-35.2 - 35.7 - 34.4 - 38.8 and 14.1 tons of dry matter (DM)/ha/year for Morado, King Grass, Cuba CT-169 , Cuba OM-22, H-1 and H-2 respectively. The Cuba OM-22 variety showed the highest production and proportion of leaves (16.6 t/DM/ha and 48.7%, respectively). The varieties with lower (P <0.005) DM yield (Morado and H-2) had higher percentage of crude protein (CP) in the plant, but lower yield of CP/h/year. Cuba OM-22 maintains high the percentage of CP with high DM yield. The growing degree-day was similar for both seasons and there was no direct relation between growing degree-day and yields, the cut age influenced the results. The yields are similar for the best varieties studied, so should be paid attention to the proportion of leaves between them and other qualities. Key words: elephant grass, growing degree-day, biomass production, Cuba.